Physiological and Multi-Omics Analysis in Leaves of Solanum americanum in Response to Cd Toxicity - Jiao Zhou; Jun-Gang Zhu; Peng Xiao; Kai-Lu Wang; Qian Xu; Meng-Xi Wu; Yuan-Zhi Pan (Plants)
Phytoremediation is a green economic method to address soil cadmium (Cd) pollution, and Solanum americanum is considered a potential phytoremediation candidate. However, the underlying Cd response mechanisms of S. americanum remain unclear. In the current study, a hydroponic experiment with 160 μmol/L Cd stress was conducted, physiological and molecular indices were measured to explore the response of S. americanum leaves to Cd stress at different time points (0, 3, and 7 days). Our findings revealed that Cd stress inhibited plant growth. Moreover, Cd stress significantly increased Cd accumulation, as well as Chla content, Chla/b, activities of SOD and POD, and elevated MDA content in the leaves. Furthermore, transcriptomics, proteomics, and metabolomics analyses revealed 17,413 differentially expressed genes (DEGs), 1421 differentially expressed proteins (DEPs), and 229 differentially expressed metabolites (DEMs). Meanwhile, integrative analyses of multi-omics data revealed key proteins involved in response to Cd stress, including POD, PAL, F5H, COMT, and CAD for phenylpropanoid biosynthesis, as well as GAPA, FBP, and FBA for photosynthesis pathways. Additionally, conjoint analyses highlighted that upregulated phenylpropanoid metabolism and photosynthesis alleviated Cd toxicity, playing vital roles in enhancing Cd tolerance in leaves. A conceptual molecular regulatory network of leaves in the response to Cd toxicity was proposed. This comprehensive study will provide detailed molecular-scale insights into the Cd response mechanisms in S. americanum.